2015
DOI: 10.4103/0300-1652.170386
|View full text |Cite
|
Sign up to set email alerts
|

Endodontic treatment of the pregnant patient: Knowledge, attitude and practices of dental residents

Abstract: Introduction:In order to control serious pulpal pain following odontogenic infections in pregnant women, endodontic treatment may become necessary. The aim of this study was to assess the perception of dentists about rendering endodontic treatment to pregnant women.Materials and Methods:This was a cross-sectional study of resident doctors in the different dental specialties in Nigeria preparing for the various levels of the fellowship examinations of the West Africa College of Surgeons and the National Postgra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Physicians should always try to reduce the stress level of the patientand the dentist should always make decisions in favor of the patients 7,16 . Few studies 11,12,17 showed that people avoid check-ups to the dentist due to fear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physicians should always try to reduce the stress level of the patientand the dentist should always make decisions in favor of the patients 7,16 . Few studies 11,12,17 showed that people avoid check-ups to the dentist due to fear.…”
Section: Discussionmentioning
confidence: 99%
“…These fears can be attributed to the ignorance of patients about root canal procedures. Patients often do not understand the nature of endodontic treatment and what it involves 7,8 . Studies in the past had highlighted the need to provide more information about it 4,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, increased consumption of carbohydrates leads to more acid formation. Also, vomiting and saliva are reduced (Enabulele and Ibhawoh, 2015). Also, pregnant women are always at high risk for caries than non-pregnant women.…”
Section: Introductionmentioning
confidence: 99%